Touch Points in University Tuition - Critical Reflections on PBL Tuition Practice at the Architecture and Urban Design Programmes at Aalborg University, Denmark - Simon Wind; Anne Kirkegaard Bejder; Gunvor Riber Larsen (Journal of Problem Based Learning in Higher Education, 2017)
This is a discussion paper that is based on the didactics reflections of three junior academics at the Architecture and Urban Design (A&UD) programme at Aalborg University. The discussion is moored in two narratives representing two typical student tuition situations. Unfolding two touch points where PBL and architectural and engineering teaching converge, this paper discusses how ‘the problem’ and ‘supervision’ at the A&UD programme are hybrid tuition focus points, where principles of PBL and more traditional tuition styles within architecture and engineering come into contact and cause didactic friction. This friction necessitates teachers and supervisors to critically reflect upon their teaching and supervision styles, and upon how ‘the problem’ is put into play in their tuition of students. The paper argues that teachers and supervisors have a heightened obligation and responsibility to monitor, assess, reflect and adjust the integration of the different teaching approaches in their hybrid tuition practices at A&UD.